Geographical variation in the trait‐based assembly patterns of multitrophic invertebrate communities. (9th June 2022) - Srivastava, Diane S.; MacDonald, A. Andrew M.; Pillar, Valério D.; Kratina, Pavel; Debastiani, Vanderlei J.; Guzman, Laura Melissa; Trzcinski, Mark Kurtis; Dézerald, Olivier; Barberis, Ignacio M.; de Omena, Paula M.; Romero, Gustavo Q.; Ospina‐Bautista, Fabiola; et al.
Abstract: It has been argued that the mechanisms structuring ecological communities may be more generalizable when based on traits than on species identities. If so, patterns in the assembly of community‐level traits along environmental gradients should be similar in different places in the world. Alternatively, geographical change in the species pool and regional variation in climate might result in site‐specific relationships between community traits and local environments. These competing hypotheses are particularly untested for animal communities. Here we test the geographical constancy of trait‐based assembly patterns using a widespread multi‐trophic community: aquatic macroinvertebrates within bromeliads. We used data on 615 invertebrate taxa from 1, 656 bromeliads in 26 field sites from Mexico to Argentina. We summarized invertebrate traits with four orthogonal axes, and used these trait axes to examine trait convergence and divergence assembly patterns along three environmental gradients: detrital biomass and water volume in bromeliads, and canopy cover over bromeliads. We found no overall signal of trait‐based assembly patterns along any of the environmental gradients. However, individual sites did show trait convergence along detrital and water gradients, and we built predictive models to explore these site differences. Sites that showed trait convergence along detrital gradients were all north of the Northern Andes. This geographical pattern may be related to phylogeographical differences in bromeliad morphology. Bromeliads with low detritus were dominated by detritivorous collectors and filter feeders, where those with high detritus had more sclerotized and predatory invertebrates. Sites that showed the strongest trait convergence along gradients in bromeliad water were in regions with seasonal precipitation. In such sites, bromeliads with low water were dominated by soft‐bodied, benthic invertebrates with simple life cycles. In less seasonal sites, traits associated with short‐term desiccation resistance, such as hard exoskeletons, were more important. In summary, we show that there are strong geographical effects on the trait‐based assembly patterns of this invertebrate community, driven by the biogeography of their foundational plant species as well as by regional climate. We suggest that inclusion of biogeography and climate in trait‐based community ecology could help make it a truly general theory. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog. Resumen: Se ha argumentado que los mecanismos que estructuran las comunidades ecológicas pueden ser más generalizados cuando se basan en los rasgos de las especies que en la identidad de las especies. Si este es el caso, los patrones de ensamblaje de las comunidades a nivel de rasgos a lo largo de gradientes ambientales deberían ser similares en distintos lugares en el mundo. Alternativamente, los cambios en el grupo de especies y la variación climática a nivel regional pueden resultar en una relación sitio‐específica entre los rasgos de las comunidades y los ambientes locales. Estas hipótesis contrastantes no han sido probadas para las comunidades de animales. Aquí, probamos la constancia geográfica de los patrones de ensamblaje basados en rasgos utilizando una comunidad multi trófica de amplia distribución: macroinvertebrados acuáticos dentro de bromelias. Utilizamos datos de 615 taxones de invertebrados de 1, 656 bromelias en 26 áreas de estudio desde México hasta Argentina. Resuminos los rasgos de los invertebrados dentro de cuatro ejes octagonal y utilizamos esos ejes para evaluar los patrones de ensamblaje de convergencia y divergencia de rasgos a lo largo de tres gradientes ambientales: biomasa de detritus y volumen de agua en las bromelias y cobertura de dosel sobre las bromelias. No encontramos ninguna señal general de patrones de ensamblaje basados en rasgos a lo largo de los gradientes ambientales. Sin embargo, sitios individuales mostraron convergencia de rasgos a lo largo de los gradientes de detritus y agua, por lo que construimos modelos predictivos para explorar estas diferencias entre sitios. Los sitios que mostraron convergencia de rasgos a lo largo del gradiente de detritus estaban al norte de los Andes del Norte. Este modelo geográfico puede ser relacionado con diferencias filogeográficas en la morfología de la bromelia. Las bromelias con bajo contenido de detritus fueron dominadas por invertebrados detritívoros colectores y filtradores mientras que bromelias con altos contenidos de detritus presentaron más invertebrados predadores y con cuerpos esclerotizados. Los sitios que tuvieron alta convergencia de rasgos a lo largo del gradiente de agua de la bromelia estuvieron en regiones con precipitaciones estacionales. En estos sitios, bromelias con bajo cantidad de agua estuvieron dominados por invertebrados bentónicos con cuerpos blandos y ciclos de vida simples. Los rasgos asociados con resistencia a la desecación a corto plazo como exoesqueletos duro fueron más importantes en sitios con menos estacionalidad. En síntesis, mostramos que hay efectos geográficos fuerte sobre los modelos de ensamblaje basados en rasgos de esta comunidad de invertebrados impulsados por la biogeografía de las especies de plantas fundacionales, así como por el clima regional. Sugerimos que la inclusión de la biogeografía y el clima en la ecología de comunidades basada en rasgos puede ayudar a hacer de esta una verdadera teoría general.